Primi appunti per una ecologia complessa dell’arte postumana - Galati, Gabriela (Scenari, 2021)
Starting from a brief genealogy of what may be considered the first posthuman artistic practices, from Marcel Duchamp to Land Art and the first Art & Technology approaches, and from an analysis of some particular artistic practices I would like to outline a research hypothesis that will be further explored in works to follow. Although the predominant tendency in the theorisations on posthuman art is to clearly separate the topics concerning art and technology from those concerning artistic practices of the living, I will begin to work on an articulation that on the one hand can contemplate the specific differences of each one of these practices, but where on the other hand the artistic practices of the living and of new media art can be part of the same landscape, or ecology: that is to say, to be understood and outlined with a methodology that allows to investigate in depth, following Jacques Derrida, that what we share as humans with the living as a whole is not only a shared passivity and finitude, but also the fact that in the case of human animals this finitude is inseparable from the prosthetic constitution of the machine of language as always already technological beings. It is in this sense that a reflection on the living must necessarily include the technological dimension and vice versa. From this point of departure we can therefore speak of a complex, if not complete, ecology of post-human art.